Janice Holt Giles : a writer's life - Stuart, Dianne Watkins (University Press of Kentucky, 1998)
In 1946, at the age of 41, Janice Holt Giles wrote her first novel. Thee years later, when her sixth novel appeared, Janice Holt Giles's works had accumulated sales of nearly two million copies. Between 1950 and 1975 she wrote twenty-four books, most of which were bestsellers, regularly reviewed in the New York Times, and selected for inclusion in popular book clubs.